Features of Internet Dialogue at the Modern Stage - Zuret Khalidovna Kobleva; Irina Asfarovna Karataban (Вестник Майкопского государственного технологического университета, 2023)
The article analyzes modern Internet technologies that have a significant impact on the process of relations between the civil society and the state, considers the possibilities of building a dialogue between government bodies with representatives of various social groups, using modern Internet technologies. Special attention is paid to the Internet communications system, as an important principle in the implementation of the policy of openness and accessibility in the activities of public authorities, the priority of which is noted in the relevant regulatory legal acts. The article reveals the mechanism of communication of citizens with state authorities and local self-government through the system of state portals. In this regard, it is necessary to highlight an important feature of the Internet dialogue at the present time: it is close interaction between the subjects of communication, which is increasing due to the modern technical characteristics of the Internet. The relevance of the article is due to the emergence of a serious scientific interest in new forms of Internet communication. The purpose of the article is to study and consider the features of the modern Internet dialogue between the subjects of communication, which is increasing due to the modern technical characteristics of the Internet. In accordance with a specific goal, the following tasks have been set and solved: - to study the concept, forms and organization of communication via the Internet; - to find out the advantages and disadvantages of virtual communication; - to consider the features of the Internet dialogue on the Internet. The practical significance of the article lies in the use of provisions and conclusions in the process of communication between the state and civil society. The methodological basis of the article includes a systematic approach, and methods of comparison and observation. Thus, an information-rich environment can act as an effective platform for the interaction of various people and social groups, representing one of the universal means of communication and information transfer. With the growth of modern computer technologies, the forms and methods of Internet communications are constantly changing and improving. It should be noted that the Internet space is a part of modern society, in which each person has the opportunity for self-realization, which, in turn, arouses great interest from scientists in this topic.